1999
DOI: 10.1046/j.1524-4725.1999.08278.x
|View full text |Cite
|
Sign up to set email alerts
|

Eccrine Syringofibroadenoma Treated with a Dual Pulse Width Flashlamp Pumped Pulsed Dye Laser

Abstract: Treatment of eccrine syringofibroadenoma with a FPDL may provide both a vascular specific injury, analogous to the treatment of verruca vulgaris, and nonspecific thermal destruction at high fluences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Excision appears to be the definitive treatment. Trauner et al reported a patient with ESFA successfully treated with a dual pulse width flashlamp pumped pulsed dye laser [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Excision appears to be the definitive treatment. Trauner et al reported a patient with ESFA successfully treated with a dual pulse width flashlamp pumped pulsed dye laser [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous regression of reactive ESFA after successful treatment of the underlying inflammatory condition has been described, corroborating the notion that reactive ESFA be regarded as an example of secondary, non-autonomous epidermal hyperplasia15. Recently, one case obtained good results for treatment using pusing pulsed dye in incurable ESFA20.…”
Section: Discussionmentioning
confidence: 59%
“…Other treatments are rarely described. Reported treatments include surgical excision and conventional destructive modalities such as cryotherapy, curettage, electrodessication, or laser (19).…”
Section: Discussionmentioning
confidence: 99%